Exploring the effect of lifestyle behaviors and socioeconomic status on atrial fibrillation: the mediating role of 91 inflammatory cytokines - Liu, Yiheng; Huang, Mingsheng; Sun, Yue; Dai, Weiran (Frontiers in Cardiovascular Medicine, 2024)
Background Atrial fibrillation (AF) is one of the most prevalent cardiac arrhythmias and has a significant economic and social burden. Whether it is associated with lifestyle behaviors and socioeconomic status is currently poorly understood. This study aimed to explore the relationship among these factors and determine the role of inflammatory cytokines. Method We investigated the causal effects of lifestyle behaviors and socioeconomic status on AF using bidirectional two-sample Mendelian randomization (MR). Instrumental variables were obtained from a publicly available genome-wide association study. A two-step MR was conducted to determine the mediating role of 91 inflammatory cytokines. Inverse variance weighted was used as the main method with four supplementary MR methods. To obtain more robust results, several sensitivity analyses were conducted. Result The results indicated that seven of the lifestyle behaviors [smoking initiation, vegetable intake, coffee consumption (cups/day), dozing, lifetime smoking index, napping, and alcohol abuse] were potential risk factors for AF. One socioeconomic status, education attainment (years of education), was causally associated with a decreased risk of AF. Moreover, we found that thymic stromal lymphopoietin, CD40l receptor, C-X-C motif chemokine 6, and C-X-C motif chemokine 11 levels mediated the causal effect, at proportions of 13.6%, 4.1%, 4.3%, and 6.9%, respectively. Conclusion Our findings provide insight into the relationship between lifestyle behaviors, socioeconomic status, and AF. Inflammatory cytokines are potential mediators of this relationship.